PENGARUH EKSTRAK RANTING AGLAIA ODORATA LOUR. TERHADAP PERKEMBANGAN PARASITOID ERIBORUS ARGENTEOPILOSUS (CAMERON) PADA INANG CROCIDOLOMIA BINOTALIS ZELLER - Sudarmo , Djoko Prijono, Syafrida Manuwoto, dan Damayanti Buchori (Universitas Lampung, 2001)
The effect of Aglaia odorata Lour. twig extract on development of a parasitic wasp Eriborus argenteopilosus (Cameron) in its host Crocidolomia binotalis Zeller. This laboratory study was conducted to evaluate the effect of ethyl acetate soluble fraction of methanolic twig extract of Aglaia odorata Lour. (Meliaceae) on the development of a parasitic wasp Eriborus argenteopilosus (Cameron) (Hymenoptera: Ichneumonidae) in its host larvae Crocidolomia binotalis Zeller (Lepidoptera: Pyralidae). Extract treatment was given through the host. C. binotalis larvae were fed broccoli leaves treated with A. odorata extract at LC25, LC50, and LC70, then were exposed to the female adults E. argenteopilosus. Mortality of the parasitized host larvae, survival of immature stages of the parasitoid in the host larvae, and longevity and fecundity of the emerging female parasitoids were recorded. The results showed that combinations of extract treatments (at LC25, LC50, and LC70) and parasitization increased the mortality of the parasitized host larvae (38,4 - 42,7%) more than twice that of the parasitized control larvae. Those extract treatments, however, did not exert any negative effects on developmental time of the parasitoid immature stages nor on some morphological characters, longevity and fecundity of the emerging female parasitoids. Thus, A. odorata extract showed promise to be integrated with the parasitoid for the control of C. binotalis.